Biodiversity, abundance, seasonal and diurnal airborne pollen distribution patterns at two different heights in Augsburg, Germany. (15th December 2021) - Kolek, Franziska; Plaza, Maria P.; Charalampopoulos, Athanasios; Traidl-Hoffmann, Claudia; Damialis, Athanasios
Abstract: Airborne pollen are the most important aeroallergens worldwide. Because of climate change, pollen seasonality and abundance have been altering significantly, raising the fundamental question: when and how much is the pollen exposure increasing? To answer this, we applied a multi-resolution study design, from bi-hourly to yearly scale, investigating the diversity, abundance and temporal occurrence of airborne pollen. The whole spectrum of airborne pollen concentrations was registered during 2015–2017, using a 7-day recording Hirst-type volumetric trap. Monitoring took place at ground-level, where we mostly commute and reside, and at the 'gold-standard' rooftop-level (12 m above ground level), at resolutions: A) bi-hourly, B) daily. The biodiversity and the relative abundance of all taxa were assessed, and the first pollen season calendars, along with circadian calendars, for Augsburg, Germany, were developed. More than 40 pollen types were identified, of which 13 were the most abundant (>0.5% relative abundance each, accounting for a total of 91.8%). Biodiversity did not present any striking differences between heights, with pollen from Urticaceae, Betula and Poaceae representing consistently more than half of the regional atmospheric biodiversity. At rooftop-level, pollen abundances often appeared to be higher, particularly for Betula, Picea and Quercus . The main pollen season extended from March to October, with the highest peak occurring April–May. At rooftop-level, the pollen seasons of most taxa were observed earlier and the overall seasons were longer. Within the day, higher pollen concentrations were observed either at midday to early afternoon (Urticaceae, Poaceae, Plantago and mostly taxa at ground-level) or night to early morning, frequently with multi-modal diurnal patterns ( Betula, Fraxinus and mostly taxa at rooftop-level). Our findings reveal that generalisation of abundance and temporal distribution patterns between ground-level and 'gold-standard' rooftop-level pollen measurements should be intensively reconsidered. While the pollen diversity and abundance may be well represented within this height range, the temporal occurrence is not, with pollen vertical variability being more important than originally anticipated. Hence, we need to reassess when and how much the relevant pollen exposure is increasing. Highlights: The first pollen calendars were elaborated in Bavaria, Germany. The whole pollen diversity was studied at two heights on bi-hourly, daily and yearly scale. Biodiversity and abundance did not change dramatically between heights. On a daily scale, pollen seasons occurred earlier or last longer at rooftop-level. On a diurnal scale, pollen occurred on average 2 h earlier at rooftop level.